1998
DOI: 10.1063/1.122012
|View full text |Cite
|
Sign up to set email alerts
|

The role of dislocation scattering in n-type GaN films

Abstract: The lateral transport in GaN films produced by electron cyclotron resonance plasma-assisted molecular beam epitaxy doped n type with Si to the levels of 1015–1020 cm−3 was investigated. The room temperature electron mobility versus carrier concentration was found to follow a family of bell-shaped curves consistent with a recently proposed model of scattering by charged dislocations. The mechanism of this scattering was investigated by studying the temperature dependence of the carrier concentration and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
283
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(315 citation statements)
references
References 9 publications
25
283
2
1
Order By: Relevance
“…It was argued that, in the case of low dopant concentrations, dislocation scattering dominates whereas impurity scattering becomes significant at high carrier concentration due to screening of the dislocation charge. [31][32][33] Therefore, the slight difference in plasmon damping in the Ga-and N-face domains can be explained by differences in threading dislocation density.…”
Section: Resultsmentioning
confidence: 99%
“…It was argued that, in the case of low dopant concentrations, dislocation scattering dominates whereas impurity scattering becomes significant at high carrier concentration due to screening of the dislocation charge. [31][32][33] Therefore, the slight difference in plasmon damping in the Ga-and N-face domains can be explained by differences in threading dislocation density.…”
Section: Resultsmentioning
confidence: 99%
“…In Si-doped GaN for the dislocation density below 10 9 cm −2 , it was reported that the majority electron mobility is mainly limited not by the dislocation density but by the doping concentration. 18 The mobility values decrease with increasing the Si-doping concentration, and they are 170, 100, and 60 cm 2 / V s for the carrier concentration of 4 ϫ 10 18 , 1 ϫ 10 19 , and 6 ϫ 10 19 cm −3 , respectively. 18 These reported majority electron mobility values agree with the minority electron mobility values derived from the EBIC results.…”
mentioning
confidence: 99%
“…18 The mobility values decrease with increasing the Si-doping concentration, and they are 170, 100, and 60 cm 2 / V s for the carrier concentration of 4 ϫ 10 18 , 1 ϫ 10 19 , and 6 ϫ 10 19 cm −3 , respectively. 18 These reported majority electron mobility values agree with the minority electron mobility values derived from the EBIC results. On the other hand, the minority hole mobilities were calculated to be 26 and 23 cm 2 / V s for the Si-doping concentrations of 4 ϫ 10 17 and 4 ϫ 10 18 , respectively.…”
mentioning
confidence: 99%
“…The dislocation density determined from this model was proved to be in good agreement with transmission electron microscopy ͑TEM͒ results. 19,20 Based on the dislocation model, the dislocation densities of samples I and III are estimated to be mid-10 9 cm Ϫ2 whereas sample II is in the low-10 9 cm Ϫ2 range. Future works on TEM and selective photoenhanced wet etching 21 experiments will be done to further elucidate the effects of types I, II, and III DBL on the reduction in dislocation density and this will be subject of a separate publication.…”
Section: Resultsmentioning
confidence: 99%